Performance analysis of a synthetic jet-microchannel hybrid heat sink for electronic cooling - Chandratilleke, Tilak; Jagannatha, Deepak; Narayanaswamy, Ramesh (IEEE, 2009)
This paper proposes a novel concept for enhancing the heat removal potential in a microchannel-based heat sinks and presents a study of its thermal performance. This technique utilises a jet mechanism that injects into the heat sink's flow passage a strong periodic fluid jet without any net mass outflow through the discharge orifice, hence termed "synthetic jet". The flow within this microchannel-synthetic jet hybrid heat sink is modelled as a 2-dimensional finite volume simulation with unsteady Reynolds-averaged Navier-Stokes equations while using the Shear-Stress-Transport (SST) k-ω turbulence model to account for fluid turbulence. For a range of conditions, the characteristics of this periodically interrupted micro fluid flow are identified while evaluating its convective heat transfer rates. The results indicate that this pulsed jet micro-heat sink can deliver heat removal rates 4.3 times higher than an equivalent heat sink without jet mechanism. The thermal enhancement is first seen to grow gently and then rather rapidly beyond a certain flow condition to reach a steady value. The proposed strategy has the unique intrinsic ability to deliver unprecedented thermal performance in micro-heat sinks without additional fluid circuits or pressure drop. The technique has application potential in miniature electronic devices where intense localised cooling is desired over a base heat load.